Identifying classes with different disability profiles amongst patients with persistent neck pain - Konsta Koivunen; Mikhail Saltychev; Juhani Juhola (Journal of Rehabilitation Medicine, 2026)
Objective: To identify latent classes with distinct disability profiles among patients with persistent neck pain using item-level responses from the Neck Disability Index, and to examine demographic, clinical, and lifestyle factors associated with class membership. Design: Cross-sectional survey-based study. Patients: 962 patients with persistent neck pain. Methods: This survey-based study included 962 patients with persistent neck pain. Latent class analysis was performed using the 10 dichotomized items of the Neck Disability Index (NDI) as indicator variables. Demographic, clinical, and lifestyle characteristics were subsequently examined across the identified latent classes. Results: The mean age was 50 (SD 32.5) years and 647 (67%) were women. Three distinct classes were identified: class with no or mild disability (47% of the sample); class with moderate disability in reading, driving, and lifting but not in personal care and concentration (15% of the sample); and class with overall severe disability (37% of the sample). Lower educational level, obesity, physical inactivity, worse pain, and lower occupational status were associated with a higher probability of belonging to the severe disability class. Conclusion: Patients with persistent neck pain appear to exhibit distinct disability profiles rather than a single uniform pattern of functional limitation. Identifying these profiles may improve the characterization of patient heterogeneity and provide a basis for future research evaluating their clinical and prognostic relevance. Further studies are needed to determine whether these profiles are reproducible in other populations and whether they have implications for treatment planning and outcomes.